KURIKULUM PENDIDIKAN TINGGI ABAD 21: HARAPAN DAN TANTANGAN - Mabrur, Hidayatul (Islamic University of Indonesia, 2017)
This article discusses the challenges of developing curriculum components in 21st century universities by looking at four core components of curriculum namely objectives, content, processes and evaluation. The article argues that these four components of curriculum are important to be developed to respond to developmental issues and innovations in the higher education curriculum. It further argues that higher education in the 21st century is increasingly demanded to continue to innovate, especially in formulating the objectives, content, process and evaluation mechanism. This is important in response to the development of science and technology, community needs, and the needs of graduate users (stakeholder needs) in the 21st century.Â Keywords: curriculum, universities, 21th century